PENGARUH KOMUNIKASI TERHADAP PENYELESAIAN TUGAS DI SUB BAGIAN PENGKAJIAN SEKRETARIAT DPRD KABUPATEN KUTAI TIMUR - Taslim, Taslim (PREDIKSI, 2016)
This study is intended to determine the effect of communication on the completion of tasks in Subdivision Assessment East Kutai Regency Secretariat therefore the researchers to formulate hypotheses "Allegedly communications have been associated with the completion of the task in the East Kutai Regency Secretariat".The timing of the research conducted in January 2016 to April 2016 for 4 (four) months. The research method in this study is quantitative, the data obtained through direct observation to the field, interviews and distributing questionnaires to the interviewees by the number of samples is 12 (twelve) of respondents.Based on calculations using the product moment coefficient known to have a strong influence among the discipline with the service and the number 0.688. This figure is interpreted as a fairly strong correlation.While testing the hypothesis generating that empirical rxy of 0.688> r xy table = 0.576. Thus the hypothesis is accepted, because there is significance (significance) between the communication of the completion of tasks in the Sub Secretariat of the East Kutai Regency.